Efficacy of disinfectants for inactivation of Ebola virus in suspension by integrated cell culture coupled with real-time RT–PCR. (July 2022) - Huang, Y.; Xiao, S.; Song, D.; Yuan, Z.
Summary: Background: Ebola virus can be transmitted by contact with environmental surfaces (fomites) contaminated with secretions and excretions from infected individuals. Due to their potential to cause a public health emergency and the absence of efficacious drugs and vaccines, a crucial intervention may involve the use of an effective virucidal agent for disinfecting contaminated surfaces. Aim: To evaluate the virucidal efficacy of three disinfectants against Ebola virus: Micro-Chem Plus detergent disinfectant cleaner (MCP), FWD, and ethanol; in suspension tests according to the Technical Standard for Disinfection of China. Methods: All products at different concentrations were tested with application times ranging from 15 s to 8 min by using a quantitative suspension test, and a comparative inactivation analysis was performed. A reduction in the virus titre of ≥4 log10 was regarded as evidence of virucidal activity. Findings: MCP and FWD, which contain dual quaternary ammonium compounds, are highly effective at inactivating the Ebola virus within 15 s of contact time, despite a slight difference between them at lower concentrations. In agreement with the literature, our results confirmed the excellent virucidal activity of medical ethanol for Ebola virus, which can reduce viral titres to background levels within 15 s at a concentration of 38% (v/v). Conclusion: These three disinfectants display sufficient inactivation efficacy for the Ebola virus at reasonably short contact times, which may be practically achieved in the field. The use of these disinfectants for decontamination in healthcare settings and laboratories could mitigate the risk of Ebola virus transmission.